Systemic Lidocaine Fails to Improve Postoperative Pain, But Reduces Time to Discharge Readiness in Patients Undergoing Laparoscopic Sterilization in Day-Case Surgery: A Double-Blind, Randomized, Placebo-Controlled Trial. Issue 3 (May 2016) - Dewinter, Geertrui Barbara Erika; Teunkens, An; Vermeulen, Kristien; Al tmimi, Layth; Van de Velde, Marc; Rex, Steffen
Abstract : Background and Objectives: Perioperative systemic lidocaine provides postoperative analgesia, decreases opioid consumption, and facilitates rehabilitation in abdominal surgery. We hypothesized that systemic lidocaine has analgesic effects in women undergoing day-case laparoscopic sterilization. Methods: Eighty women were randomized in this prospective, double-blind trial to receive either lidocaine (intravenous bolus of 1.5 mg/kg at induction of anesthesia, followed by an infusion of 1.5 mg · kg −1 · h −1, which was continued until 30 minutes after arrival at the postanesthesia care unit [PACU]) or placebo. The primary end point was the proportion of patients with a numeric rating scale (NRS) of greater than 3, 30 minutes after arrival at the PACU. Secondary outcomes included total opioid consumption, postoperative pain scores, incidence of postoperative nausea and vomiting, and time to readiness for discharge. This clinical trial was registered (Eudra CT 2011-001315-31). Results: Thirty minutes after PACU admission, the proportion of patients with an NRS score of greater than 3 did not differ between the groups (lidocaine group: 59% vs placebo group: 58%). The postoperative NRS for pain over the entire observation period was not significantly different between lidocaine and placebo groups (mean, 3.1 [SD, 0.7] vs 2.8 [SD, 0.6]; P = 0.4). Groups did not differ with respect to perioperative opioid consumption. Patients in the placebo group suffered significantly less from nausea (NRS: 0.1 [SD, 0.1] [placebo] vs 0.3 [SD, 0.1] [lidocaine]; P = 0.02) and required less postoperative nausea and vomiting rescue medication (1 patient in the placebo group vs 7 in the lidocaine group; P = 0.03). The time to meet hospital discharge criteria was significantly lower in the lidocaine group (median, 177 minutes [range, 96–408 minutes] vs 221 minutes [range, 121–420 minutes]; P = 0.02). The mean lidocaine plasma levels at the end of IV lidocaine infusion was 2.5 (SD, 1.1) μg/mL. Conclusions: In laparoscopic sterilization, systemic lidocaine reduces time to readiness for hospital discharge.